Maradona As A Versatile Media Figure: A Study On Turkish Press. - Kabaş, Denizcan; Güler, Şükrü (Funes. Journal of narratives and social sciences, 2022)
The death of world football legend Diego Armando Maradona was on the top of the agenda of Turkish media as well as all over the world. Maradona has found a place in Turkish society at different times not only as a football player or manager but also as a rebellious, funny, and astonishing figure. This study consists of two parts in total: The first section focuses on media figures in the globalized world and it provides examples of Maradona with Turkey crossroads. Here, it is investigated by which representations the physical existence is established. Although the identity of the players or coaches worked in Turkey, though, points of intersection with Turkey in recent history, have been of crucial importance for the transport of these attributes until today. In the second part of the study, contents published in the Turkish printing press are investigated during their dissemination in the first week after the death of Maradona,. The study is focused on newspapers, columns, and thematic magazines; The memory, evaluation, and exemplification related to Maradona are evaluated by the “content analysis” methods. Findings of the study; Maradona is not only a footballer, but also a powerful figure with an ideological point of view, and is a celebrity personality that has always been curious; they, with the historical intersections corresponding to the projection of the recent history of Turkey and axles, are forming the meaning of the name Maradona. As a result, it can be said that the examined newspapers and magazines published memories by focusing on Maradona’s different identities.